Closure Operators on Complete Almost Distributive Lattices-III - Rao, Calyampudi Radhakrishna; Undurthi, Venugopalam (Bulletin of the Section of Logic, 2015)
In this paper, we prove that the lattice of all closure operators of a complete Almost Distributive Lattice L with fixed maximal element m is dual atomistic. We define the concept of a completely meet-irreducible element in a complete ADL and derive a necessary and sufficient condition for a dual atom of Φ (L) to be complemented.